MANAJEMEN PESERTA DIDIK DALAM MENINGKATKAN PRESTASI AKADEMIK DI SEKOLAH FULL DAY SCHOOL (STUDI MULTISITUS DI SMP YIMI GRESIK DAN SMP MUHAMMADIYAH 12 GRESIK) - Tria Heni Agustina; Mochamad Nursalim; Ayu Wulandari; Amrozi Khamidi; Kaniati Amalia; Syunu Trihantoyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT Heni Agustina, Tria. 2025. Student Management in Improving Academic Achievement in Full Day Schools (A Multi-Site Study at YIMI Gresik Junior High School and Muhammadiyah 12 Gresik Junior High School). Master’s Program in Educational Management, Faculty of Education, State University of Surabaya. Advisors: (I) Prof. Dr. Mochamad Nursalim, M.Si. and (II) Dr. Ayu Wulandari, S.Pd., M.Pd. Knezevich (1961) defines student management or pupil personnel administration as a service that focuses on the arrangement, supervision and service of students in class and outside the class such as introduction, registration, individual services such as overall development of abilities, interests, needs until they mature in school. This study focuses on how student management improves academic achievement in full day schools at SMP YIMI Gresik and SMP Muhammadiyah 12 Gresik. This study uses a qualitative approach with a descriptive method (Bogdan & Biklen, 1982)), with student management that includes planning, organizing, implementing, evaluating the results of learning implementation appropriately, and the results increase according to the expected target. The data sources for this study are principal, curriculum vice principal, student affairs vice principal, teachers, students, and relevant documents. Data collection techniques use in-depth interviews, observation and documentation. Data validity check with triangulation of sources, techniques, and time. The results of the study indicate that: student management is well managed by the principal in organizing the initial planning of the KBM SK, additional task SK, achievement coaching SK, teacher training can be implemented to improve competence, learning well, and the principal evaluates teacher performance, learning outcomes, and student academic achievement results, students increase, students are more enthusiastic about learning, students can learn happily and comfortably, the average knowledge score of class IX report cards increase, and academic achievement (academic competitions) also increases at the Regency, Provincial, National and International levels. Keywords: Full Day School, Student Management, Academic Achievement.